Technology for Reduction of Nitrogen Oxide Emissions at Pulverized Coal Burning - Dunaevska, N.I.; Nehamin, M.M.; Bondzyk, D.L. (Science and Innovation, 2024)
To assess the influence of thermochemical preparation of anthracite on the formation of nitrogen oxides, a 3D numerical model of the TPP-210A boiler`s furnace has been created for standard and modified burners. The calculations have showed a decrease in NOx concentration along the vertical extent of the furnace and in the amount of unburnt coal for the modified burners as compared with the standard ones.